Design universal em conjuntos habitacionais: estudos dos fatores de inserção urbana em conjuntos Minha Casa Minha Vida - Carolina Furtado Pereira (2018)
This work contains an investigation about the factors of urban insertion in housing projects financed by the Minha Casa Minha Vida (my house, my life) - MCMV program and the possible link with the foundations of Universal Design. The consideration about the products of the MCMV program on actual sites of small cities should be viewed critically as an opportunity to avoid the continuity of inaccessible models of housing production existing across the country. There are two steps in the research. The first explored the theoretical-conceptual basis on Universal Design, accessibility, inclusive society, meanings of autonomy and independence, among other definitions linked to the housing issue in Brazil. In the second stage, the empirical universe of the investigation contains five case studies and involves housing complexes in Bom Despacho, Campo Belo and Formiga, small-medium cities of Minas Gerais. Through direct observation and analysis of the characteristics of five housing complexes, interviews were conducted with professionals responsible for the approval of projects in the Municipal Works Departments. The results represent a complex scenario of local accessibility problems that are combined with the urban insertion factors in all the case studies. Such evidence invalidates the application of the current model of public funding as a solution for the production of housing in large scale in Brazil, since that overlooks the importance of Universal Design as an essential parameter of accessibility.